Gaze Strategies in Driving–An Ecological Approach - Lappi, Otto (Frontiers in Psychology, 2022)
Human performance in natural environments is deeply impressive. The human advantage over AI and robotics for real-world dynamic tasks suggests that our brain may be using strategies and techniques for organizing perception and action that are different from current AI. Experimental techniques such as eye tracking may be useful to understand the cognitive basis of this performance. Eye tracking can be deployed even “in the wild”, but there is always a balance to strike between ecological complexity and experimental control. One way to reconcile these conflicting demands is to look for natural, real-world tasks and behavior that are rich enough to be interesting yet sufficiently constrained and well-understood to be replicated in simulators and the lab. One such domain - where the human advantage can still be observed - is driving. Eye movement research in driving has revealed robust patterns that can be reliably identified and replicated in the field, and reproduced in the lab. The purpose of this review is to cover the basics of what is known about these gaze behaviors, and some of their implications for understanding visually guided steering. The paper is written in a way that would be accessible and interesting to the non-specialist, without oversimplifying the complexity of real-world visual behavior. Part of a Research Topic on Gaze Strategies in Closed Self-paced tasks, this aspect of the driving task is discussed, and it is emphasized why it is important to carefully separate the visual strategies driving (quite closed and self-paced) from visual behaviors relevant to other forms of driver behavior (an open-ended menagerie of behaviors). The phenomena reviewed will be of interest to those working on any domain where visual guidance and control with similar task-demands is involved (e.g. many sports). Even more generally, the ecological approach, and the way the connection between “lab” and “real world” can be spanned in this research is of interest to anyone keen to develop more ecologically representative designs for studying human gaze behavior.